Clinical Characteristics and Diagnostic Prediction of Severe Fever with Thrombocytopenia Syndrome and Rickettsiosis in the Co-Endemic Wakayama Prefecture, Japan - Kan Teramoto; Shinobu Tamura; Kikuaki Yoshida; Yukari Inada; Yusuke Yamashita; Masaya Morimoto; Toshiki Mushino; Daisuke Koreeda; Kyohei Miyamoto; Nobuhiro Komiya; Yoshio Nakano; Yusaku Takagaki; et al. (Medicina, 2023)
Background and Objectives: The Wakayama prefecture is endemic for two types of tick-borne rickettsioses: Japanese spotted fever (JFS) and scrub typhus (ST). Severe fever with thrombocytopenia syndrome (SFTS) is a tick-borne hemorrhagic viral disease with a high mortality rate and is often difficult to differentiate from such rickettsioses. SFTS cases have recently increased in Wakayama prefecture. For early diagnosis, this study aimed to evaluate the clinical characterization of such tick-borne infections in the co-endemic area. Materials and Methods: The study included 64 febrile patients diagnosed with tick-borne infection in Wakayama prefecture between January 2013 and May 2022. Medical records of 19 patients with SFTS and 45 with rickettsiosis (JSF, n = 26; ST, n = 19) were retrospectively examined. The receiver operating curve (ROC) and area under the curve (AUC) were calculated to evaluate potential factors for differentiating SFTS from rickettsiosis. Results: Adults aged ≥70 years were most vulnerable to tick-borne infections (median, 75.5 years; interquartile range, 68.5–84 years). SFTS and rickettsiosis occurred mostly between summer and autumn. However, no significant between-group differences were found in age, sex, and comorbidities; 17 (89%) patients with SFTS, but none of those with rickettsiosis, experienced gastrointestinal symptoms such as vomiting, abdominal pain, and diarrhea. Meanwhile, 43 (96%) patients with rickettsiosis, but none of those with SFTS, developed a skin rash. The AUCs of white blood cells (0.97) and C-reactive protein (CRP) levels (0.98) were very high. Furthermore, the differential diagnosis of SFTS was significantly associated with the presence of gastrointestinal symptoms (AUC 0.95), the absence of a skin rash (AUC 0.98), leukopenia <3.7 × 109/L (AUC 0.95), and low CRP levels < 1.66 mg/dL (AUC 0.98) (p < 0.001 for each factor). Conclusions: Clinical characteristics and standard laboratory parameters can verify the early diagnosis of SFTS in areas where tick-borne infections are endemic.